2018
DOI: 10.1213/ane.0000000000002749
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Intraoperative Motor-Evoked Potential Monitoring to Prevent Postoperative Spinal Cord Injury in Thoracic and Thoracoabdominal Aneurysm Repair: An Audit of the Japanese Association of Spinal Cord Protection in Aortic Surgery Database

Abstract: MEP monitoring was not significantly associated with motor deficits at discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…The authors conclude that "SSEP and MEP are both important monitoring measures to predict and prevent spinal cord ischemia during distal aortic repairs." Their study clearly demonstrates a very strong negative predictive value associated with SSEP and MEP monitoring and confirms the results from an earlier study, 4 from 2 systematic reviews, 5,6 and from 1 multicenter trial, 7 all of which demonstrated a low prevalence of SCII if the MEP signals remained or returned to normal during the operative period, with a specificity that exceeded 95%. In the latter studies, [5][6][7] however, considerably more variability in the ability to predict the occurrence of permanent SCII was noted when the signals did not return to normal at the end of the procedure.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The authors conclude that "SSEP and MEP are both important monitoring measures to predict and prevent spinal cord ischemia during distal aortic repairs." Their study clearly demonstrates a very strong negative predictive value associated with SSEP and MEP monitoring and confirms the results from an earlier study, 4 from 2 systematic reviews, 5,6 and from 1 multicenter trial, 7 all of which demonstrated a low prevalence of SCII if the MEP signals remained or returned to normal during the operative period, with a specificity that exceeded 95%. In the latter studies, [5][6][7] however, considerably more variability in the ability to predict the occurrence of permanent SCII was noted when the signals did not return to normal at the end of the procedure.…”
supporting
confidence: 83%
“…Their study clearly demonstrates a very strong negative predictive value associated with SSEP and MEP monitoring and confirms the results from an earlier study, 4 from 2 systematic reviews, 5,6 and from 1 multicenter trial, 7 all of which demonstrated a low prevalence of SCII if the MEP signals remained or returned to normal during the operative period, with a specificity that exceeded 95%. In the latter studies, [5][6][7] however, considerably more variability in the ability to predict the occurrence of permanent SCII was noted when the signals did not return to normal at the end of the procedure. As noted previously, it was not possible in the study of Tanaka and colleagues 3 to determine the positive predictive value of evoked potential monitoring from the data presented.…”
supporting
confidence: 83%
“…Next, a report found that motor-evoked potential monitoring did not contribute to improving motor impairment in patients who had undergone descending and thoracoabdominal aortic repair. 26 However, the evidence for the usefulness of motor-evoked potential monitoring remains controversial, and some advocate this practice for spinal cord ischemia and injury. 27,28 The Japanese Circulation Society's Guidelines for Diagnosis and Treatment of Aortic Aneurysm and Aortic Dissection recommend TEVAR for patients with traumatic aortic injury, patients with complicated acute type B aortic dissection, and situations in which there is available support from a surgical team.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, electrophysiological monitoring is affected by anesthetics and hypothermia [24], is incapable of monitoring in the preoperative or immediate postoperative setting, and requires continuous presence of a technologist and/or neurologist. Thus, it is unclear whether current intraoperative neurophysiological monitoring in aortic [25] or spine surgery [26] influences outcome.…”
Section: Introductionmentioning
confidence: 99%